Family Subjective Well-Being of Health Workers Women During The Covid-19 Pandemic : Family Subjective Well-Being of Health Workers Women During The Covid-19 Pandemic - Euis Sunarti; Dinda Kamilah; Husniyah Almas; Siti Pitriani (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2020)
This survey research aims to analyze the factors that influence, as well as test differences in the subjective well-being of the families of women health workers during the Covid-19 pandemic, according to the two types of working time (Stable and shift). This study involved 110 families (47 stable and 63 shift working hours) from Jabodetabek area, which was selected by non-probability random sampling. Data were collected in April 2020. The results showed that women health workers with stable working hours had significantly higher subjective well-being, financial management, and marriage satisfaction, but otherwise had lower husband-wife interactions and work and family problems than women with shift working hours. The results of the main regression model showed that family well-being was influenced positively by coping strategies, marital satisfaction, and husband's education. Meanwhile, the derivative regression model that analyzes the variable components showed that family well-being was influenced positively by a component of marriage satisfaction, a component of family interaction, implementation of family time management, and husband's education; but negatively influenced by family income and husband's age. In general, the family of women health workers during the Covid-19 pandemic was expected to develop various efforts to increase marriage satisfaction and the family's subjective well-being.